HUBUNGAN ANEMIA, IMT DAN MOBILISASI DINI DENGAN PENYEMBUHAN LUKA SECTIO CAESAREA DI RSUD KAYUAGUNG - Robiatun, Robiatun; Romadhon, Muhammad (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
The presence of complications or complicating factors in the delivery mass is a risk factor for maternal death so that medical action is necessary as an effort to save the mother and child. Sectio Caesarea is an action for delivery of the fetus through an incision through the abdominal wall and uterus (Dorland Dictionary, 2017). According to the World Health Organization the average standard for Caesarean section (SC) operations is around 5-15%. Data from the WHO Global Survey on Maternal and Perinatal Health 2018 shows 46.1% of all births via cesarean. According to statistics on 3,509 cases of CS compiled by Peel and Chamberlain, indications for CS are 21% of fetal hip disproportion, 14% of fetal distress, 11% of placenta previa, 11% of previous CS, 10% of fetal position abnormalities, preeclampsia and 7% of hypertension . The purpose of this study was to determine the relationship between anemia, body mass index and early mobilization simultaneously with post-section caesarean wound healing at Kayu Agung Hospital in 2021. This study used an analytical survey method with a cross sectional approach. This research was conducted by RSUD Kayu Agung. With a total sample of 58 respondents, the sampling technique used was the accidental sampling technique. The variables studied were independent (anemia, body mass index and early mobilization) and dependent (post section caesarean wound healing). The results of the chi-square test for anemia variable obtained value = 0.002, body mass index variable value = 0.042, and early mobilization variable value = 0.021 this indicates that there is a significant relationship between anemia, body mass index and early mobilization with healing. Caesarean section post-section wound at Kayu Agung Hospital in 2022